Aryl-platform-based tetrapodal 2-iodo-imidazolium as an excellent halogen bond receptor in aqueous medium. Issue 10 (16th January 2019) - Chakraborty, Sourav; Maji, Siddhartha; Ghosh, Rajib; Jana, Rajkumar; Datta, Ayan; Ghosh, Pradyut
Abstract : The graphic shows a halogen bonding interaction between a tetrapodal platform attached to a 2-iodo-imidazole unit and bromide in water. Abstract : An acyclic tetrapodal receptor (L 4+ -I )(4PF6 ) 4− comprised of four 2-iodo-imidazolium motifs showed moderate to strong binding of halides through halogen bonding interactions in organic and aqueous media, with these binding levels established by performing isothermal titration calorimetry studies. Importantly, single crystals suitable for X-ray diffraction studies were obtained from both water and an acetonitrile–water binary solvent mixture, and exhibited halogen bonding interactions in the solid state.